2017
DOI: 10.14689/ejer.2017.71.11
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Socio-cultural factors on females passing through Higher Education in Pakistan

Abstract: Purpose: Educated females play an important role in the social and economic development of a country. The aim of the study was to assess the problems facing females before entering higher education, and then after education when joining professions. Research Methods: Using a higher education survey questionnaire, data were collected from 2188 female respondents including students (n=2018) and teachers (n=170) from government colleges and universities spread over four districts of the Pakistan province of Punja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The study concluded that improving the educational status of females in Pakistan is essential for overall national development. Shaukat and Pell (2015) explored the social and personal issues faced by women in higher education. The study recommended enhancing the socio-cultural environment and improving educational standards for female education to bring about positive changes across all sectors.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The study concluded that improving the educational status of females in Pakistan is essential for overall national development. Shaukat and Pell (2015) explored the social and personal issues faced by women in higher education. The study recommended enhancing the socio-cultural environment and improving educational standards for female education to bring about positive changes across all sectors.…”
Section: Review Of Literaturementioning
confidence: 99%
“…So one of the reasons that make women down is the lack of role models in the field of educational leadership. Shaukat and Pell (2017) state that females in leadership positions face maledominant culture in the workplace causing conflict between professional and cultural obligations. The small number of women leaders in the field of educational leadership can make it difficult for resourceful networking among female principals (Kowalski and Stouder, 1999).…”
Section: Support Systemmentioning
confidence: 99%
“…Several studies have uncovered the impacts of the socio-economic and cultural hurdles that Pakistani women face before entering, during, and even after leaving higher education, and when they join professions and are exposed to dominant male culture. (Shaukat & Pell, 2017).…”
Section: Literature Review and Rationale Of The Researchmentioning
confidence: 99%